Development and evaluation of a dynamic code visualization system for C programming education: The PVLS approach - Lai, Chien-Hung; Lin, Pei-Wen; You, Shu-Han (Social sciences & humanities open, 2025)
—Programming is a fundamental skill in higher education, yet many beginners struggle with understanding program logic and execution flow. Traditional teaching methods and existing visualization tools often fail to provide dynamic, real-time execution tracking from student-written code. This study aimed to develop and evaluate the Programming Visual aided Learning System (PVLS) that dynamically generates flowcharts and process comprehension from students' own code to enhance programming comprehension and debugging skills. Participants were 37 first-year C programming students from a Taiwanese university. A three-week pre-post experimental design was employed: Week 1 (pretest), Week 2 (PVLS intervention), and Week 3 (posttest and survey). Programming and process architecture scores were collected from coding tasks, and students completed a 19-item Likert-scale questionnaire on system usability, visualization effectiveness, and learning perceptions. Paired samples t-tests and descriptive statistics were used for analysis. Results showed significant improvements in total scores (p < .001) and programming performance (p = .014), but no significant gains in process comprehension. Questionnaire results indicated that students valued PVLS's usability, visualization features, and progress tracking, though motivational gains were modest (∼30 % reporting increased interest or confidence). PVLS was associated with students' code-writing and debugging abilities but showed limited association with process comprehension and motivation. Future research should explore extended interventions, richer interactive features, and larger, more diverse samples to validate its broader applicability.